1985
DOI: 10.1099/0022-1317-66-12-2627
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide Fingerprint Analysis of Coxsackievirus A10 Isolated in Japan

Abstract: SUMMARYEight coxsackievirus A10 strains isolated in 1978 and in 1981 and 1982 from patients with hand, foot-and-mouth disease and with herpangina at a dispensary in Matsue city were compared by RNA fingerprinting techniques. The oligonucleotide maps of the four 1978 isolates were related to each other by 85 to 93% with respect to their large T1 oligonucleotides. In contrast, the oligonucleotide maps of the four 1981 and 1982 isolates were very different from each other. Co-electrophoresis experiments revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…We assumed this was due to formation of secondary structures among some of the T1-digested oligonucleotides, which affected the relative efficiency of the kinase reaction. Similar observations have been noted for other RNA viruses (Frisby 1977, Stephenson & Ter Meulen 1982, Kamahora et al 1985, Kusters et al 1987. The pres- ence of several small genetic subpopulations (a result of the high mutation rate of RNA viruses) in addition to the dominant population (quasispecies) may also be a factor (Steinhauer et al 1989b).…”
supporting
confidence: 56%
“…We assumed this was due to formation of secondary structures among some of the T1-digested oligonucleotides, which affected the relative efficiency of the kinase reaction. Similar observations have been noted for other RNA viruses (Frisby 1977, Stephenson & Ter Meulen 1982, Kamahora et al 1985, Kusters et al 1987. The pres- ence of several small genetic subpopulations (a result of the high mutation rate of RNA viruses) in addition to the dominant population (quasispecies) may also be a factor (Steinhauer et al 1989b).…”
supporting
confidence: 56%
“…Previous study indicated that other enteroviruses were frequently detected in specimens collected from patients who presented with HFMD. For instance, CVA10 were isolated from patients with HFMD in New Zealand in 1957 [ 19 ]. The first report of HFMD caused by CVA6 was documented in Finland in 2008, after that, reports of outbreaks caused by CVA6 have increased worldwide such as in Taiwan, France and Guangzhou [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…HFMD epidemics have primarily been associated with CVA16 or enterovirus 71 infections; those caused by enterovirus 71 have occurred more frequently in Southeast Asia and Australia in recent years ( 12 ). Reportedly, CVA10 has been found in minor outbreaks; other coxsackievirus A types have been found in only sporadic cases of HFMD ( 2 , 3 ). In general, CVA6 infections have been seldom detected and mostly in association with herpangina ( 13 , 14 ).…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of HFMD have been mainly caused by 2 types of enterovirus A species, coxsackievirus (CV) A16 (CVA16) or enterovirus 71 ( 1 ). Some outbreaks have been associated with CVA10, but only sporadic cases involving other members of the enterovirus A species have been reported ( 2 , 3 ). …”
mentioning
confidence: 99%